2021
DOI: 10.1029/2020gh000359
|View full text |Cite
|
Sign up to set email alerts
|

Health Impact Assessment of the 2020 Washington State Wildfire Smoke Episode: Excess Health Burden Attributable to Increased PM2.5 Exposures and Potential Exposure Reductions

Abstract: Major wildfires starting in the summer of 2020 along the west coast of the United States made PM 2.5 concentrations in this region rank among the highest in the world. Washington was impacted both by active wildfires in the state and aged wood smoke transported from fires in Oregon and California. This study aims to estimate the magnitude and disproportionate spatial impacts of increased PM 2.5 concentrations attributable to these wildfires on population health. Da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 37 publications
0
46
0
4
Order By: Relevance
“…Large areas of the BR are sparsely populated and do not have permanent air pollution monitoring posts. The lack of stationary observation posts in the vast territories makes it especially relevant to search for opportunities to assess atmospheric air pollution and its danger for the population of small settlements, remote from large centers, with a developed infrastructure for monitoring the quality of the environment and providing emergency medical care in emergency situations [37]. Krstic and Henderson, after analyzing data on smoke and clouds from the Canadian Terra-MODIS 2000-2007, suggested that the average daily measurements of the optical thickness of aerosols can be used to represent the smoke levels in the area and make urgent decisions about the evacuation of the population [11].…”
Section: Discussionmentioning
confidence: 99%
“…Large areas of the BR are sparsely populated and do not have permanent air pollution monitoring posts. The lack of stationary observation posts in the vast territories makes it especially relevant to search for opportunities to assess atmospheric air pollution and its danger for the population of small settlements, remote from large centers, with a developed infrastructure for monitoring the quality of the environment and providing emergency medical care in emergency situations [37]. Krstic and Henderson, after analyzing data on smoke and clouds from the Canadian Terra-MODIS 2000-2007, suggested that the average daily measurements of the optical thickness of aerosols can be used to represent the smoke levels in the area and make urgent decisions about the evacuation of the population [11].…”
Section: Discussionmentioning
confidence: 99%
“…Smoke from wildfires also affects local and distant air quality (the 2019-2020 Australian wildfires affected New Zealand and South America) (Nguyen et al, 2021), and smoke from Siberian fires has affected North America . The full health impact of the 2019-2020 wildfires will not be known for some time due to lags in the availability of health data, but current assessments estimate around 90 increased deaths in Washington State (Liu et al, 2021) in 2020, and over 400 additional deaths and a few thousand increased hospitalizations from the 2019-2020 bushfires in Australia (Borchers Arriagada et al, 2020). Because these studies rely on concentration-response functions from non-wildfire air pollution studies, we would expect the number of deaths related to wildfire smoke to rise when using a potentially steeper concentration-response function for wildfire smoke (Aguilera et al, 2021;Kiser et al, 2020).…”
Section: Insight 3: Climate Change Forces Fire Extremes To Reach New Dimension With Drastic Impactsmentioning
confidence: 99%
“…It is determined by debugging in the simulation process. The third step was logistic regression analysis (Liu & Austin, 2021). Logistic stepwise regression was used to analyze the relationship between spatial distribution and driving factors of land use types.…”
Section: Clue-s Modelmentioning
confidence: 99%